Quantitative inventory and analysis of the green areas in Lavras-MG and index evolution - Furtini Boldrin, Karina Volpi; Gontijo Garcia, Cecília Souza; de Oliveira Paiva, Patrícia Duarte; de Carvalho, Larissa Martiniano (Ornamental Horticulture, 2016)
The green area index is one of the parameters used to scale the life’s quality of a city. Thus, the objective was to carry out the survey of green area index from Lavras-MG, in two different periods, with an interval of 10 years, making a comparative analysis of the index evolution in this period. It was carried out the assessment of the number of city squares, as well as its area and calculate the green area index. It was considered appropriate for this index, public areas located in urban area and over 70% of the permeable area. For determine this index, it was calculated the sum of the total area of the squares divided by the number of inhabitants of the city. It is concluded that green area index in Lavras-MG is 0.42 m²/ inhabitant. There was an increase of 12% compared to the diagnosis realized in 2001, but lower than that proposed by the Brazilian Society for Urban Forestation, 15 m²/inhabitant.